Oral manifestations associated with inflammatory bowel disease and early endoscopic findings in patients with spondyloarthritis - Andrés Alvarado-Julio; Katherin Chumacero-Palma; María Rosa Buenahora; Viviana Parra-Izquierdo; Mónica Monsalve; Ana María Torres; Lorena Chila-Moreno; Cristian Flórez-Sarmiento; Alejandro Ramos-Casallas; Juliette De Avila; Juan Manuel Bello-Gualtero; Diego Jaimes; et al. (BMC, 2022)
Abstract Background and aims Spondyloarthritis (SpA) is a group of autoinflammatory disorders, of which the primary extra-articular manifestation is inflammatory bowel disease (IBD). The oral cavity being a part of gastrointestinal tract, is significantly compromised in IBD, and in many cases, it is the first site of clinical manifestations of IBD. This study aimed to identify changes in the oral mucosa associated with the onset of IBD and their association with endoscopic/histological findings. Materials and methods The study assessed 80 patients with SpA and 52 healthy controls. Oral, rheumatological, and gastroenterological assessments were performed. The ileocolonoscopy was performed via digital magnification chromoendoscopy. The statistical analysis consisted of Chi-square, Fisher's exact, and multiple correspondence discriminant analysis tests. Results From the disease cohort, 63.0% patients showed oral lesions (p = 0.050). These manifestations ranged from gingivitis (55.0%, p = 0.001), aphthous stomatitis (3.8%, p = 0.091), angular cheilitis (2.6%, p = 0.200), and perioral erythema with scaling (1.3%, p = 0.300). All patients who presented with alterations in colonic mucosa also had oral lesions associated with IBD (p = 0.039), specifically gingivitis/aphthous stomatitis (p = 0.029). Conclusion The patients with SpA without IBD present significant oral signs and symptoms. Gingivitis seems to be the most relevant because of its associations with early endoscopic and histological findings. Clinical relevance An integral approach to the diagnostic tests that includes evaluations of oral, rheumatological and gastroenterological tissues may favor timely attention and improve patients' quality of life.